The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/su15021130
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Influence of the Disturbance Caused by Traversing Cross-Type Deep Foundation Pit Excavations

Abstract: Accurately recognizing the influence of excavation disturbance on the traversing cross-type deep foundation pit of the subway, determining the active range of the disturbance, and reasonably arranging the structure within its range can effectively ensure the safety of the project and save resources to achieve the goal of sustainable development. A three-dimensional model was established using the soil small strain hardening model to examine the subway deep foundation pit project in the CBD (central business di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Soft soil is generally characterized by a certain structure, high sensitivity, low strength, and low structural strength. After the excavation of foundation pits, perimeter unloading or dynamic loads can reduce the strength of soft soil and increase deformation, which has an adverse efect on the surrounding environment around the pit inversely [12]. To fully investigate the changes in mechanical parameters, such as yield stress, undrained shear strength, compression index, and consolidation coefcient of soft soil in the Kunming area after disturbance, the structural properties of soft soil were analyzed by using the e − log p curve, the e − p curve, and compression index data.…”
Section: Research Methods and Ideasmentioning
confidence: 99%
“…Soft soil is generally characterized by a certain structure, high sensitivity, low strength, and low structural strength. After the excavation of foundation pits, perimeter unloading or dynamic loads can reduce the strength of soft soil and increase deformation, which has an adverse efect on the surrounding environment around the pit inversely [12]. To fully investigate the changes in mechanical parameters, such as yield stress, undrained shear strength, compression index, and consolidation coefcient of soft soil in the Kunming area after disturbance, the structural properties of soft soil were analyzed by using the e − log p curve, the e − p curve, and compression index data.…”
Section: Research Methods and Ideasmentioning
confidence: 99%
“…Gao et al [13], through analyzing monitoring data from the excavation of an underground diaphragm wall, discovered that the surface settlement around the circular underground diaphragm wall is primarily influenced by the excavation depth. Wang et al [14] found in the analysis of excavation disturbance on a subway crossing with a cross-shaped deep foundation pit that the interaction between the crossshaped intersection structure and the surrounding soil is affected by the repeated unloading disturbance during excavation, soil arching effects, and changes in boundary conditions. The horizontal displacement of the retaining structure and surface settlement differed significantly from the observations of single-pit excavation.…”
Section: Introductionmentioning
confidence: 99%